Fabricação digital: uma análise crítica - fortalecendo a cooperação por meio da fabricação digital - Flavia Ballerini (2017)
This research proposes to analyze the Digital Fabrication as a process of design integrated to the processes of industrial production that has as a common means the digital codification and its most recent appropriations in architecture and design. The objective of the research is to search for a critical appropriation of what has been produced in the Digital Fabrication laboratories that may be able to bring benefits to the architecture and related areas, through a reexamination of the potentialities of learning through the resumption of materiality, that in the conventional processes of design, which are reproduced with the use of the computer, ends up being lost the materiality and moving towards the alienation of those involved in the design process, so this thesis aims at autonomy and emancipation. From there, we seek a critical dialogue with the vanguard of the digital manufacturing architecture, presenting as hypothesis a proposal of critical, shared and bottom-up appropriation that can be implemented in the teaching and practice of architecture - the from hybrid, digital and analog, shared, democratic and social endowment experiences. Based on this hypothesis, we seek to deepen our research into the growing movements of Maker and Hackerspace since the 1980s, which are a reinvention of Do-It-Yourself (DIY) movements, transformed into Do-It-Together (DIT). From this, the research shows two strands or models of appropriation of the Digital Fabrication as the Fabrication laboratory (Fab Lab) of the Massachusetts Institute of Technology (MIT) and the Architectural Association Visitig School (AAVS). It seeks to take a critical approach to both, choosing the Fab Lab model as an example that is closer to what we propose as a synthesis: the use of Digital Manufacturing laboratories in architecture schools, based on a learning model based on cooperation and knowledge sharing , both technical and political. The first objective is to mobilize cooperation between people through technology: learning to cooperate with one another. For this critical appropriation, the thesis presents the technology of the Digital Fabrication within its economic-political and social context, which traces its historical matrices to the Industrial Revolution and the capitalist mode of production, arriving at the open source that, from of the 1980s, opens up the potential of using this technology outside the factories, reaching until today with its enormous disruptive potential in all fields of research and knowledge.